2014
DOI: 10.4103/0976-237x.137963
|View full text |Cite
|
Sign up to set email alerts
|

An innovative technique for root coverage using pedicled buccal fat pad

Abstract: Various etiological factors are associated with gingival recession which may be anatomical, physiologic, or pathologic factors. Several root coverage procedures have been described to manage the gingival recession. However, it has been found that root coverage procedures in Miller's Class III and IV gingival recession have a poor prognosis with current techniques. A newer predictable technique, pedicled buccal fat pad (PBFP) has been introduced in cases of severe gingival recession. The buccal fat pad (BFP) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
0
9
0
4
Order By: Relevance
“…This is the first randomized controlled clinical trial to evaluate buccal fat pad as a grafting alternative for the treatment of GRs, more specifically minor GRs (the Miller Class I and II recessions) in esthetic area. The use of buccal fat tissue as a grafting alternative has recently been outlined in case-reports describing the use of pedicled BFPG in the treatment of Miller Class IV (6,11) and Class III (7) GRs. In both cases excellent cosmetic results were reported.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first randomized controlled clinical trial to evaluate buccal fat pad as a grafting alternative for the treatment of GRs, more specifically minor GRs (the Miller Class I and II recessions) in esthetic area. The use of buccal fat tissue as a grafting alternative has recently been outlined in case-reports describing the use of pedicled BFPG in the treatment of Miller Class IV (6,11) and Class III (7) GRs. In both cases excellent cosmetic results were reported.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, Kumari et al [15] used the same technique to cover a Miller Class III defect in a maxillary right molar and obtained a 4 mm gain in the attachment level. Agarwal [6] also applied the technique in a maxillary molar with class IV gingival recession and obtained clinical attachment level and keratinized tissue gain. Ercan et al [12] described two clinical cases, where the first one showed a gain of 7 mm in the attachment level, reducing the gingival recession to 4 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Different surgical techniques such as free gingival graft, flap repositioning, and connective tissue graft have been used in the treatment of gingival recessions. Treatments with pedicled buccal fat pad grafts are also described in the literature with satisfactory results regarding root coverage, clinical attachment level, and keratinized tissue gain [6,7]. However, the use of nonpedicled buccal fat pad grafts is still poorly described [8].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical attachment gain was 4 mm at 6 months. Finally, in 2014, Agarwal et al (11) reported a case and established this technique for treating a Miller IV recession defect. They were able to achieve partial root coverage, with a 4-mm attachment gain.…”
Section: Discussionmentioning
confidence: 99%